Pengaruh Penambahan Ikan Kembung Terhadap Sifat Organoleptik Dan Kadar Air Nugget Ampas Tahu - I Gde Narda Widiada; Iketut Swirya Jaya; Dwi Yulia Estika Sari (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background : According to Mahmud, etal. (2009), Tofu is a solid waste for soybean manufactured. Each of 100 gram contains 67 kcal of energy, 5 grams of protein, 21 grams of grease, and 81 grams of carbohydrates. Dregs tofu can be used as an ingredient in manufacture of food productions which is called nugget. Nugget dregs tofu is a product from the soybean residue by adding the spices and mixed with a binder. To improve the nutritional value of the protein, it needs to add the mackerel’s meat.  Objective : To know the organoleptic properties (color, smell, taste, and texture) and water content of nuggets dregs tofu by adding mackerel’s meat.  Methode : By design studies using experimental studies with a completely randomized design (CRD) one factor by adding the mackerel’s meat which has five  treatment such as; 15%, 25%, 35%, 45% and 55%. Each treatment was repeated for three times. The parameters were observed in the study include organoleptic properties such as color, smell, taste, texture and water content nuggets dregs tofu mackerel. The analysis of data using Anova test followed by using Tukey test.  Result : By adding the mackerel’s meat has a significant effect on the taste, smell and texture of  nuggets dregs tofu (p<0.05) but had no effect on the color and the moisture content (p>0.05). The score of taste obtain from panelists are 3,12 to 3,84 (like), the smell of value is 3,00 to 3,84 (like), teksture value is 3,28 to 3,76 (like). The score of color obtain from panelists are 3,36 to 3,64 (like) and the water content with an average value from  35,17% to 39,01%.   Conclusion : By adding the mackerel’s meat has a significant effect on the smell, taste and texture of  nuggets dregs tofu (p<0.05) but had no effect on the color and the moisture content (p>0.05).